117k views
5 votes
What is the conjugate?

a - √a-1

UREGENT PLEASE HELP

2 Answers

3 votes

Answer:

the conjugate of
a -√(a-1) \ = a + √(a -1)

Explanation:

Given;


a - √(a-1)

Conjugate of
a -√(x) \ \ \ is \ \ a \ + \ √(x)

let (a - 1) = x

a - √x = a + √x


a -√(a-1) \ = a + √(a -1)

Therefore, the conjugate of
a -√(a-1) \ = a + √(a -1)

Check


(a -√(a-1)) *(a+√(a-1) ) = a^2 + \ a√(a-1)\ - \ a√(a-1) - (a-1)\\\\(a -√(a-1)) *(a+√(a-1) ) = a^2 - (a-1)\\\\(a -√(a-1)) *(a+√(a-1) ) = a^2 -a+1

The result is a rational number, hence
a + √(a-1) \ \ is \ \ conjugate \ of \ \ a -√(a-1)

User Gouldos
by
3.7k points
2 votes

Answer:


a+√(a-1)

Explanation:

The conjugate of an expression of the form:


z=a+b (1)

is another expression of the form:


z=a-b (2)

In the same way, if your expression is
z=a-b, the conjugate is
z=a+b.

You have the following expression:


a-√(a-1)

by comparing with the equations (1) and (2) you can take a=a and b=√a-1. Thus, you have the expression z = a - b. The conjugate is z = a + b. Then, you can conclude that the conjugate is:


a+b=a+√(a-1)

User HVNSweeting
by
4.7k points